Relative efficacy and tolerability of vortioxetine versus selected antidepressants by indirect comparisons of similar clinical studies. (December 2014) - Llorca, Pierre-Michel; Lançon, Christophe; Brignone, Mélanie; Rive, Benoît; Salah, Samir; Ereshefsky, Larry; Francois, Clément
Abstract Introduction: Vortioxetine is an antidepressant with multimodal activity which has shown efficacy in major depressive disorder (MDD) patients in six of ten short-term, randomized, placebo-controlled trials (completed end 2012). Methods: We performed meta-regression analyses to indirectly compare vortioxetine to seven marketed antidepressants with different mechanisms of action. To ensure study comparability, only experimental drug and placebo arms from placebo-controlled registration studies were included in primary analyses. The main outcomes were efficacy (standardized mean difference in change from baseline to 2 months on primary endpoint [MADRS/HAM-D]), and tolerability (withdrawal rate due to adverse events). Results: For efficacy, estimates of treatment effect (negative estimates favor vortioxetine) for vortioxetine versus comparators were: agomelatine, −0.16 (p = 0.11); desvenlafaxine, 0.03 (p = 0.80); duloxetine, 0.09 (p = 0.42); escitalopram, −0.05 (p = 0.70); sertraline, −0.04 (p = 0.83); venlafaxine IR/XR, 0.12 (p = 0.33); and vilazodone, −0.25 (p = 0.11). For tolerability, all but one combination was numerically in favor of vortioxetine (odds ratio < 1), although not all differences were statistically significant: agomelatine, 1.77 (p = 0.03); desvenlafaxine, 0.58 (p = 0.04); duloxetine, 0.75 (p = 0.26); escitalopram, 0.67 (p = 0.28); sertraline, 0.30 (p = 0.01); venlafaxine, 0.47 (p = 0.01); and vilazodone, 0.64 (p = 0.18). Sensitivity analyses did not significantly alter antidepressant effect estimates or relative ranking. Conclusion: These meta-regression data show that vortioxetine offers a comparable or favorable combination of efficacy (measured by MADRS/HAM-D) and tolerability (measured by withdrawal rate due to adverse events) versus other antidepressants in registration studies in MDD. Alternative methods like mixed-treatment comparison and inclusion of all randomized studies and active reference arms may provide complementary information to this analysis (more evidence but also more heterogeneity). Key messages: Indirect comparisons based on registration studies allow a useful comparison between a recently approved antidepressant and an approved drug. Vortioxetine offers a comparable or favorable combination of efficacy (measured by MADRS/HAM-D assessments) and tolerability (measured by withdrawal rate due to adverse events) versus other antidepressants in registration studies in MDD.